Pemilihan Karyawan Terbaik menggunakan Metode Profile Matching pada Koperasi Tunas Wanita Abadi - Fadila Nurhastuti Dila; Anna Mukhayaroh (LPPM Universitas Bina Sarana Informatika, 2022)
Abstrak - Koperasi Tunas Wanita Abadi merupakan perusahaan koperasi simpan pinjam, berdiri sejak tahun 2000 dengan jumlah anggota 10 orang yang dibentuk oleh sekelompok ibu-ibu rumah tangga dan bertujuan ingin membantu meningkatkan kesejahteraan keluarga mereka khususnya dan masyarakat pada umumnya, yang berlokasi di daerah Jakarta dimana karyawan yang bekerja dibawah aturan ditentukan oleh perusahaan tersebut. Dalam penelitian penentuan karyawan terbaik di Koperasi Tunas Wanita Abadi bertujuan untuk membantu Koperasi Tunas Wanita Abadi dalam memilih karyawan terbaik. Metode yang digunakan dalam penelitian ini adalah metode Profile Matching, secara umum proses kerja metode Profile Matching adalah membandingkan selisih nilai antara profil posisi yang disebut dengan Gap.Kata kunci : Sistem pendukung keputusan, Koperasi, Profile Matching.Abstract - Tunas Wanita Abadi Cooperative is a savings and loan cooperative business entity. Tunas Wanita Abadi Cooperative was founded in 2000 with an initial number of 10 members, which was formed by a group of housewives and aims to help improve the welfare of their families in particular and society in general. The Tunas Wanita Abadi Cooperative is located in the Jakarta area where employees who work under the rules are determined by the company. In this study, the determination of the best employees at the Tunas Wanita Abadi Cooperative aims to help the Tunas Wanita Abadi Cooperative in selecting the best employees. The method used in this research is the Profile Matching method, in general the work process of the Profile Matching method is to compare the difference in values between the position profiles which is called the Gap. The Profile Matching method uses several stages and formulations in the calculation which include gap mapping, weighting, calculation and grouping of core and secondary factors, calculation of total value, and calculation of ranking determination. By using the profile matching method, Tunas Wanita Abadi Cooperative can make decisions in selecting the best employees who will later get a reward in the form of a salary increase.Keywords: Decision support systems, Cooperatives, Profile Matching